ANALISIS RASIO ARUS KAS DALAM MENGUKUR TINGKAT LIKUIDITAS PT ACE HARDWARE INDONESIA TBK - Lasminiasih Lasminiasih; Kayla Azizah (Jurnal Aplikasi Perpajakan, 2026)
This study aims to determine and analyze the liquidity level of PT Ace Hardware Indonesia Tbk based on its cash flow statements for the 2022–2024 period. A quantitative descriptive method was employed, utilizing documentation and literature review approaches. The study relies on secondary data specifically financial statements, cash flow statements, and income statements obtained from the company's official website for the 2022–2024 period. Data analysis was conducted using cash flow ratio analysis, comprising the Operating Cash Flow to Current Liabilities Ratio (AKO), Cash Flow to Interest Coverage Ratio (CKB), Cash Flow to Total Liabilities Ratio (TH), and Cash Flow to Net Income Ratio (AKB). The results indicate that PT Ace Hardware Indonesia Tbk's cash flow ratios fluctuated during the 2022–2024 period; however, on average, the company demonstrated a good level of liquidity. The AKO, CKB, and AKB ratios fell into the "good" category as they met the assessment criteria, whereas the TH ratio remained in the "poor" category, indicating a need to improve the company's ability to meet its total obligations using operating cash flow.